A Thorough Study on Thixoformability of the Cooling Slope Cast 7075 Feedstocks: Step-by-Step Optimization of the Feedstock Production and Thixoforming Processes - Acar, Serhat; Guler, Kerem Altug (SPRINGER INT PUBL AG, 2023)
The semi-solid metal forming techniques have been researched for a long time to obtain near-net shape products from aluminum alloys. Most of the effort was devoted to the casting alloys such as A356 and A380 to develop an alternative technique for high pressure die casting process. In this study, the cooling slope casting technique, which is an unorthodox approach to produce semi-solid feedstocks for wrought aluminum alloys, and the results of the following thixoforming processes were investigated thoroughly for 7075 aluminum alloy. According to the parameters studied and obtained results, the lowest possible casting temperature and mild tilt angle parameters were found to give the best outcomes for the produced feedstocks' physical and microstructural properties. No significant difference was observed depending on the slope length due to the employed low superheat during casting processes. Reheating processes of the produced feedstocks revealed that gradual depletion of Al from the intergranular region and the migration of Cu to the Al-depleted zones forms the partial melt, and the average grain size of the reheated specimens dramatically increases after 40 min of reheating at selected reheating temperature. The average shape factor, grain size, and density values of the specimen selected for thixoforming processes were around 0.82, 96 mu m, and 2.67 g/cm(3), respectively. After the thixoforming processes, the maximum hardness attained was around 120 HB and a gradual decrease was observed by increasing reheating durations in both measured hardness and density values. The tensile properties were also investigated, and the results were found promising after the optimization of the forming pressure and reheating duration except for the elongation values.
Keywords: 7075 alloy; cooling slope casting; thixoforming; semi-solid forming; MICROSTRUCTURE; Metallurgy & Metallurgical Engineering